2016
DOI: 10.1371/journal.pone.0145946
|View full text |Cite
|
Sign up to set email alerts
|

Aldosterone Induces Renal Fibrosis and Inflammatory M1-Macrophage Subtype via Mineralocorticoid Receptor in Rats

Abstract: We aimed to evaluate macrophages heterogeneity and structural, functional and inflammatory alterations in rat kidney by aldosterone + salt administration. The effects of treatment with spironolactone on above parameters were also analyzed. Male Wistar rats received aldosterone (1 mgkg-1d-1) + 1% NaCl for 3 weeks. Half of the animals were treated with spironolactone (200 mg kg-1d-1). Systolic and diastolic blood pressures were elevated (p<0.05) in aldosterone + salt–treated rats. Relative kidney weight, collage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
56
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(60 citation statements)
references
References 47 publications
3
56
1
Order By: Relevance
“…Hepatic non-parenchymal cells were isolated and analyzed by flow cytometry for CD68, CD86, and CD163 expression. We combined these markers to define hepatic macrophage phenotypes as being classically (M1-like, CD68 [10,34]. We found that the proportion of M1-like hepatic macrophages significantly increased whereas the proportion of M2-like macrophages significantly decreased in fibrotic livers compared with healthy controls (Fig.…”
Section: Splenectomy Reverses the M1-dominant Hepatic Macrophage Phenmentioning
confidence: 91%
“…Hepatic non-parenchymal cells were isolated and analyzed by flow cytometry for CD68, CD86, and CD163 expression. We combined these markers to define hepatic macrophage phenotypes as being classically (M1-like, CD68 [10,34]. We found that the proportion of M1-like hepatic macrophages significantly increased whereas the proportion of M2-like macrophages significantly decreased in fibrotic livers compared with healthy controls (Fig.…”
Section: Splenectomy Reverses the M1-dominant Hepatic Macrophage Phenmentioning
confidence: 91%
“…To evaluate statistical significance for normalized protein quantification between three groups, Kruskal-Wallis with Dunn's post-hoc tests were used. In accordance with prior studies studying aldosterone ( 21 , 84 88 ) and SGK1 ( 89 ), whole-cell lysates data were normalized to α-tubulin. Furthermore, in this study, α-tubulin levels were unaffected by aldosterone treatment, as relative to control, α-tubulin quantification was 0.88 for aldosterone and 0.89 for aldosterone + GSK-650394 in iWT-TRPM7 cells.…”
Section: Methodsmentioning
confidence: 99%
“…There was an intense inflammatory response in the kidneys as evidenced by increased macrophage infiltration in the interstitium, as well as activation of myofibroblasts and profibrotic cytokines such as CTGF and its downstream modulator SMAD2. Aldosterone may contribute to the renal inflammation and injury via modulation of cytokine expression, which promotes inflammatory cell infiltration and albuminuria in hypertension‐driven renal injury (Blasi et al., 2003; Martín‐fernández et al., 2016). In addition, this may be due to upregulation of mineralocorticoid receptor expression in various vascular beds including the renal microcirculation (Delano & Schmid‐Schönbein, 2004), as well as modulating macrophage function (Rickard et al., 2009; Usher et al., 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The dose of spironolactone applied in experimental research in rodent models is often well in excess of that used clinically, generally equating using an allometric conversion, to a relative human dose of 550 mg/day or more for an average 70‐kg person (Barrera‐Chimal et al., 2012; Han et al., 2006; Klanke et al., 2008; Taira et al., 2008). Additionally, doses are typically administered at the onset, or prior to onset, of hypertension or kidney insult (Barrera‐Chimal et al., 2012; Fujisawa et al., 2004; Martín‐fernández et al., 2016) and not orally administered. Furthermore, dosing is often for a relatively short time period (less than 2 weeks) (Barrera‐Chimal et al., 2012; Klanke et al., 2008; Ortiz et al., 2007) whereas in humans dosage may be continued for years.…”
Section: Introductionmentioning
confidence: 99%